The effect of the activation of phosphoric ester cellulose particles on the electrorheological properties of anhydrous ER fluids - 안병길; 최웅수; 권오관; 문탁진 (한국윤활학회, 2001)
The electrorheological (ER) behavior of suspensions in silicone oil of phosphoric ester cellulose powder (average particle size : 17.77 mum) was investigated at room temperature with electric fields up to 2.5 kV/mm. For development of anhydrous ER fluids using at wide temperature range, it was sought the effect of activation time of phosphoric ester cellulose particles on the ER activities. Anhydrous ER fluids based on the phosphoric ester cellulose particles made from cellulose particles treating in chemical solution of 2M phosphoric acid and 4M urea and heating at 150 degreesC were measured. After activating the phosphoric ester cellulose anhydrous ER fluids at 120 degreesC, not only analysis of dispersing cellulose particles but also electrorheological characteristics of ER fluids such as dielectric constant, current density, electrical conductivity and rheological properties were studied. Activation time had a large influence to ER properties of anhydrous ER fluids based on phosphoric ester cellulose. As the activation time went by, particle size and number of dispersing particles, electrical properties, dynamic yield stress on electric field, initial apparent viscosity (eta (o)) and electrorheological effect (tau (A) / tau (0)) of phosphoric ester cellulose ER fluids increased with increasing activation time at 120 degreesC till activation time over 5 hours.